Pengaruh likuiditas, sales growth, firm size, arus kas operasi, CEO duality, dan intellectual capital terhadap financial distress pada perusahaan sektor healthcare di Bursa Efek Indonesia periode 2018-2022 - Mala Sari, Erminda Eka; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2024)
Financial distress is when a company experiences difficulty meeting its financial obligations. This condition can cause the company to go bankrupt. This research aims to determine the effect of liquidity, sales growth, company size, operating cash flow, CEO duality, and intellectual capital on financial distress in health sector companies on the Indonesia Stock Exchange for the 2018-2022 period. The type of data used is quantitative data sourced from secondary data. The population in this study were health sector companies on the Indonesia Stock Exchange for the period 2018 - 2022. The sampling technique used saturated samples, and 17 companies were obtained as samples for the research. Data were analyzed using logistic regression and calculated using IBM SPSS 25. The results of this study show that liquidity, as proxied by the current ratio (CR), has a significant and negative effect on financial distress. Meanwhile, sales growth, company size, operating cash flow, CEO duality, and intellectual capital do not have a significant effect on financial distress. Companies in the health sector must always pay attention to increasing liquidity values because increasing company liquidity contributes to reducing the potential for financial difficulties. To maintain liquidity stability, companies can carry out various proactive efforts, and inventory management can be optimized to prevent excessive accumulation or shortages that have the potential to disrupt liquidity. Efficient management of receivables is also key, with the implementation of prudent credit policies and monitoring of overdue debts to ensure timely cash receipts.